Connecting children with birth defects to health and social service programs: A collaboration between the Texas Birth Defects Registry and agency social workers. Issue 1 (14th November 2022) - Betancourt, Dayana; Canfield, Mark A.; Ethen, Mary K.; Shumate, Charles; Drummond‐Borg, Margaret; Kubenka, Christina; Palacios, Jessica; Agopian, A. J.
Abstract: Background: Timely referral to services for children born with birth defects can improve health outcomes. Birth defects surveillance registries may be a valuable data source for connecting children to health and social service programs. Methods: Population‐based, state‐wide data from the Texas Birth Defects Registry (TBDR) at the Texas Department of State Health Services (DSHS) were used to connect children 9–18 months old, born with select birth defects with DSHS social workers. The social workers reviewed developmental milestones and referred children and their families to various health and social service programs. We tabulated the proportions of children meeting milestones and referral characteristics by referral program type and type of birth defect. Results: Social workers reached 67% (909/1, 362) of identified families. Over half of children (54%, 488/909) were not meeting the developmental milestones for their age. Social workers provided over 3, 000 program referrals, including referring 21% (194/909) of children to Early Childhood Intervention (ECI) and 28% (257/909) to case management. Conclusion: Our results illustrate a method of leveraging a birth defects surveillance system for referral services. Given the large number of referrals made, our findings suggest that birth defects registries can be a valuable source of data for referring children to programs.